Meningkatkan Hasil Belajar Produk Kreatif dan Kewirausahaan Melalui Penerapan Model Pembelajaran Berbasis Portofolio - Nurlaela Nurlaela (Journal on Education, 2023)
Efforts to improve the quality of learning by improving teaching methods and as a teacher's reference to create more interesting and varied learning in the learning process so as to increase student interest and motivation in learning can influence the improvement of student outcomes in learning. The purpose of this research is to find out the increase in the learning value of Creative Products and Entrepreneurship with the application of a portfolio-based learning model at SMKN 1 Cirebon. This research was conducted in two stages, namely the observation stage and the implementation stage. This research uses Classroom action research, which is carried out in three cycles and several stages, namely planning, action, observation, and reflection. This Classroom Action Research (PTK) uses a portfolio-based learning model with learning methods in the form of inquiry methods and group discussions. In each implementation cycle sequence with the steps and goals set. At the final stage of the cycle implementation, a test was conducted to measure students' understanding and abilities. The data collection technique used is a test. The test is given at the end of each cycle. In cycle I and cycle II, students were given a multiple choice test consisting of 10 questions. In cycle III, students are given 20 multiple choice questions. In the first cycle of students who have met the Minimum Completeness Criteria (KKM) of 26.47%. In cycle II, 38.24% of students were able to achieve the Minimum Completeness Criteria (KKM). The highest increase was in cycle III, 76.47% of students were able to achieve the Minimum Completeness Criteria (KKM).